Three new species of the primitively segmented spiders from Mt Yuelu, Hunan, China (Mesothelae, Liphistiidae) - Li, Dengqing; Liu, Hao; Xu, Xin (Zootaxa, 2019)
We diagnose and describe two Songthela and one Vinathela species of the primitively segmented spiders, Liphistiidae, as new to science based on morphological characters and molecular data: Songthela pyriformis sp. nov. (male, female), Songthela shuyuan sp. nov. (male, female), Vinathela nenglianggu sp. nov. (male, female), which were collected at Mt Yuelu in Changsha, Hunan Province, China. To facilitate future identification of our species, we also provide the GenBank accession numbers of the DNA barcode gene, cytochrome c oxidase subunit I (COI) for all type specimens and the evidence of genetic distances based on COI for three new species.